PERAN APARATUR PEMERINTAH TERHADAP PENERBITAN E-KTP DI KELURAHAN BARANTI KECAMATAN BARANTI KABUPATEN SIDENRENG RAPPANG - Fitri, Ade; S, Sapri; Ibrahim, Monalisa (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2025)
The purpose of this study is to determine the role of government officials in the administration of e-KTP in Baranti Village, Baranti District, Sidenreng Rappang Regency and the factors that influence it. This study employed a quantitative approach with a descriptive approach. Data collection involved observation, questionnaires, and literature review. The study population consisted of 244 individuals, with a sample size of 76 respondents determined using the Slovin formula. Data analysis employed descriptive statistics and simple linear regression with the aid of SPSS. The results of the study show that the role of government officials is in the good category with an average percentage of 73%. The factors influencing the e-KTP service include awareness at 75%, regulations at 80%, organization at 76.8%, task skills at 78.2%, and facilities and infrastructure at 78.2%, with an overall average percentage of 77.6%, which is categorized as good. The R Square (R²) value of 55.4% indicates that the variable of government officials’ role affects the e-KTP service, while the remaining 44.6% is influenced by other variables outside this research. The t-test shows that the value of tcount is greater than ttable (11.041 > 1.660), meaning Ho is rejected and Ha is accepted, which indicates significance. Thus, the role of government officials has a significant effect on the e-KTP issuance service in Baranti Village, Baranti District, Sidenreng Rappang Regency.